Clinical and Ultrasonographic Assessment of Nail Psoriasis: A Comprehensive Study - Esposito, Maria; Magnanimi, Lina Maria; Antonetti, Paolo; De Berardinis, Andrea; Pellegrini, Cristina; Vagnozzi, Emanuele; Bruni, Manfredo; Gianneramo, Camilla; Cipriani, Paola; Fargnoli, Maria Concetta; Barile, Antonio; Ruscitti, Piero (Dermatology Practical & Conceptual, 2025)
Introduction: In patients with plaque type psoriasis (PSO), the progression to psoriatic arthritis (PsA) exacerbates the disease's impact and increases disability risk. Nail psoriasis (NP) affects up to 90% of PSO patients with a wide spectrum of clinical features and is a significant predictor of enthesitis, often associated with early PsA stages. Objective: This study aimed to clinically and ultrasonographically evaluate nail units in PSO patients, focusing on differences between those with/without PsA and those with/without onychopathy. Methods: Sixty patients were enrolled (23/60 PSO-37/60 PSO and PsA). PSO and PsA patients were evaluated and compared as well as patients with/without diagnosis of nail psoriasis in this cross-sectional single-center study. Nail abnormalities were evaluated by high frequency ultrasound (HFUS) using high frequency probes (27 MHz). After a descriptive assessment, the Nail Psoriasis Severity Index (NAPSI) and the Brown University Nail Enthesis Scale (BUNES) were used to clinically and ultrasonographically assess nails. Results: HFUS evaluation identified a spectrum of nail and blood flow alterations. Nail disease was characterized by median NAPSI 16 (range 28), median BUNES morphometry 1.5 (range 0.9), and median BUNES power Doppler (PD) 2.2 (range 4.03). Among the studied sample, 43/60 (71.7%) presented nail psoriasis, with 69.7% presenting coexisting PsA as compared to PSO patients (30.3%) (p = 0.04). Conclusion: Our findings highlight the importance of close collaboration between dermatologists and rheumatologists in the evaluation of PSO patients, taking advantage of both clinical and ultrasonographic assessment of nail damage.